Using IEPC Strategy to Improve Students’ Reading Comprehension at Grade VIII.4 of SMP Negeri 3 Pekanbaru - Warman, Liya Astarilla Dede (J-SHMIC : Journal of English for Academic, 2016)
The purposes of this research are to describe and explain to what extent IEPC strategy could improve students’ reading comprehension at grade VIII.4 of SMP Negeri 3 Pekanbaru and the factors that influenced the change of their reading comprehension by using IEPC strategy at grade VIII.4 of SMP Negeri 3 Pekanbaru. This research is classroom action research, every cycle consisted of four fundamental aspects namely, planning, action, observation, and reflection. This research consisted of three cycle, where in each cycle consisted of fourmeetings. The four meetings in one cycle involving three meetings for teaching reading by using IEPC strategy and one meeting for post-test at the end of every cycle.The participants of this research were the researcher, a collaborator and the students of grade VIII.4 of SMP Negeri 3 Pekanbaru totalling 40 students. The instruments of this research were reading comprehension test, an observation sheet, field note and interview.There were two findings of this research: (1) IEPC strategy could improve the students’ reading comprehension; (2) Teaching material and media, class activity, class management, and teacher’s approach were the factors that could influence the change of students’ reading comprehension.